COVID‐19 diagnosis and management: a comprehensive review. (13th May 2020) - Pascarella, Giuseppe; Strumia, Alessandro; Piliego, Chiara; Bruno, Federica; Del Buono, Romualdo; Costa, Fabio; Scarlata, Simone; Agrò, Felice Eugenio
Abstract: Severe acute respiratory syndrome coronavirus (SARS‐CoV)‐2, a novel coronavirus from the same family as SARS‐CoV and Middle East respiratory syndrome coronavirus, has spread worldwide leading the World Health Organization to declare a pandemic. The disease caused by SARS‐CoV‐2, coronavirus disease 2019 (COVID‐19), presents flu‐like symptoms which can become serious in high‐risk individuals. Here, we provide an overview of the known clinical features and treatment options for COVID‐19. We carried out a systematic literature search using the main online databases (PubMed, Google Scholar, MEDLINE, UpToDate, Embase and Web of Science) with the following keywords: 'COVID‐19', '2019‐nCoV', 'coronavirus' and 'SARS‐CoV‐2'. We included publications from 1 January 2019 to 3 April 2020 which focused on clinical features and treatments. We found that infection is transmitted from human to human and through contact with contaminated environmental surfaces. Hand hygiene is fundamental to prevent contamination. Wearing personal protective equipment is recommended in specific environments. The main symptoms of COVID‐19 are fever, cough, fatigue, slight dyspnoea, sore throat, headache, conjunctivitis and gastrointestinal issues. Real‐time PCR is used as a diagnostic tool using nasal swab, tracheal aspirate or bronchoalveolar lavage samples. Computed tomography findings are important for both diagnosis and follow‐up. To date, there is no evidence of any effective treatment for COVID‐19. The main therapies being used to treat the disease are antiviral drugs, chloroquine/hydroxychloroquine and respiratory therapy. In conclusion, although many therapies have been proposed, quarantine is the only intervention that appears to be effective in decreasing the contagion rate. Specifically designed randomized clinical trials are needed to determine the most appropriate evidence‐based treatment modality. Abstract :